Efficacy of combination therapy of triazole and echinocandin in treatment of invasive aspergillosis: a systematic review of animal and human studies - Zhang, Ming; Sun, Wen-Kui; Wu, Ting; Chen, Fei; Xu, Xiao-Yong; Su, Xin; Shi, Yi (Journal of Thoracic Disease, 2014)
Objective: The effectiveness of the combination therapy of triazole and echinocandin in treatment of invasive aspergillosis (IA) remains controversial. The objective of this systematic review was to assess the efficacy of combination therapy of triazole and echinocandin in treatment of IA. Methods: Relevant articles on the combination therapy of triazole and echinocandin in IA, including the animal studies and clinical studies from January 1966 to October 2013, were searched on Web of Science, PubMed and Cochrane Library. The prolongation of survival of the combination therapy of triazole and echinocandin in IA was performed as risk ratio (RR) with 95% confidence interval (95% CI). Results: Nine animal studies with a total of 1,582 animals and five clinical trials totaling 872 patients were included. The survival of the included animal studies with combination therapy was significantly prolonged compared with echinocandin alone [RR =2.26, (95% CI, 1.79-2.87; P